Mechanical properties of AlCrTiSiN coatings developed by cathodic arc for protection applications - Panich, Nurot (2013)
The aim of this work is to fabricate and develop the innovative ceramic coatings for protection applications with both high hardness and coating adhesion particularly performing in extremely environmental conditions. In this study, nanocomposite AlCrTiSiN coatings were developed and deposited on Carbide coupons (WC with Co binder) substrate using Cathodic Arc Deposition techniques. The resultant coatings were evaluated with respect to fundamental mechanical properties such as hardness, modulus and coating adhesion. It was found that the nanomposite AlCrTiSiN coatings has a good adhesion to the substrate and retained extremely high hardness as superhard coatings with hardness values above 50 GPa.